Strengthening Religious Character to Prevent Bullying Behavior Students in Elementary Schools - Iyoh Maspiroh; Haryanto Haryanto (UM Purwokerto Press, 2023)
Bullying is a behavior that disturbs students in schools both at the elementary and secondary levels. This behavior has many negative impacts and influences on learning outcomes and students' mental development. This study aims to determine the relationship between strategies for instilling religious character in preventing bullying or bullying behavior in elementary school students. This research method uses the method of literature review. The findings from this study are that the cultivation of religious character can prevent bullying in elementary schools by carrying out several strategies, namely exemplary, learning, empowering and acculturating, strengthening and assessing.